A comparative analysis of the South African and Global Tourism Competitiveness models with the aim of enhancing a sustainable model for South Africa - Maharaj, S. (Journal of Economics and Behavioral Studies, 2014)
The quality of life of society as a whole is to a considerable extent determined by the role of government. South African society is characterised by the presence of a wide gap between the rich and the poor. This is exacerbated by the presence of poverty, HIV/AIDS, crime, corruption and exploitation. Governments attempt to address these contradictions are encapsulated in various policies that detail in accurate form, the needs of the majority of South Africans. Whilst policies depict the needs of the majority of South Africans, these needs remain undelivered. The void between the formulation of policy and service delivery has been most severely felt by the poor. Policy implementation is the responsibility of central, provincial and local government. The policy on tourism has been identified as one of the major players in resolving the impasse that is experienced by government. According to South Africa’s National Tourism Sector strategy (2011 & 2016) the country’s tourism’s economic contribution is set to increase from R318, 16 billion by 2015 to R499 billion by 2020. The challenge however, remains in harnessing Tourism policy in a way that addresses the past and current contradictions. Legislative provisions, policies and plans have set the tone in terms of the direction that tourism should be heading. Public sector institutions at national, provincial and local levels have equipped themselves to develop and enhance the tourism industry in such a way that it resonates with the South African tourism imperatives. This places within context the role of public organisations and its capacity to deliver in terms of government’s national imperative. The tourism industry is complex with a range of different stakeholders. There is an inextricable link between the tourism and hospitality industries. This paper attempts to improve on the South African tourism competitiveness with the expressed intention of enhancing growth and sustainability.